DISSEMINATION OF THE CONCEPT OF PERSONAL INDIVIDUATION IN MODERN PHILOSOPHY AND PSYCHOLOGY (THEORETICAL AND HISTORICAL OVERVIEW OF THE CONCEPT DEVELOPMENT) - Lescinskaite, Irma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article aims to reveal the concept of Individuation. Individuation is perceived as a conscious decision to constantly create one’s qualitative life by realizing one’s creative strengths and personal human needs. It can and is also perceived as a (self)educational process, which occurs in an educational environment that is suitable for the self-expression and individuation of a person. The following article reveals the philosophical and psychological approaches towards the concept of personal individuation. The concepts of individuation of the following authors are being reviewed: I. Kant, F. Schiller, F. Nietzsche, J. Dewey, R. Rorty, G. Jung, C. Rogers and A. Maslow.